EFFECT OF THE USE OF LIQUID SMOKE CONCENTRATION OF DIFFERENT QUALITY OF KEPAH’S (Meterix meterix) LIQUID SMOKE DURING STORAGE AT ROOM TEMPERATURE - Maya Ervin Putri; Syahrul '; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to know the influence of different used liquid smokeduring saving kepah's smoke clam on the room's temperature. This research usedto experiment method that analized quality during saving on 0, 3, and 6 days. Themethod used to RAK non factorial method, with 2 varian of contration of liquidsmoke 1% k1 and 2% K2 and period of saving 0, 3, 6 days. K2 with contraction2% of organoleptic value is appreance of the kepah's smoke clam which iscomplete, clean, brown, the specific light with average of value 7,2, odorless,enough smoke without the smell disturbing with 7,21 values, deligious flavor with6,31 values, solid texture, dry enough between two messes with 8,03 values.thecomposition of chemestry of water kadar 21,44%, protein 13,14%, fatty 3.42%,proxide 1,23 meq/1000g sample and to analize of micobiologi is total of colonialbacteria (TPC) (4,2 x104) bacteria. The period of saving kepah's clam is 6 days.Keyword : Kepah’s, Liquid Smoke, Quality